2020
DOI: 10.1002/emp2.12227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preadministered and coadministered lidocaine for treating pain and distress associated with intranasal midazolam administration in children: A randomized clinical trial

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In this study, it appears there was no benefit to adding lidocaine and in fact, it appears to worsen complaints at the time of administration. Our findings are consistent with O'Connell et al who reported that pain and distress were comparable when intranasal lidocaine was administered before or concurrently with INM, but that intranasal lidocaine alone also caused significant pain and distress [17]. A combined dose would allow a single atomized dose compared to potential distress caused by two separate doses of Xylocaine (lidocaine) and midazolam.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, it appears there was no benefit to adding lidocaine and in fact, it appears to worsen complaints at the time of administration. Our findings are consistent with O'Connell et al who reported that pain and distress were comparable when intranasal lidocaine was administered before or concurrently with INM, but that intranasal lidocaine alone also caused significant pain and distress [17]. A combined dose would allow a single atomized dose compared to potential distress caused by two separate doses of Xylocaine (lidocaine) and midazolam.…”
Section: Discussionsupporting
confidence: 91%
“…Rather, it has prompted the study of different strategies for treating this pain so that children can still benefit from its favorable properties (e.g. rapid onset, needle‐free administration, effective anxiolysis), such as with the pre‐treatment or co‐administration with lidocaine 57,60‐63 14,48,49,51 .…”
Section: Discussionmentioning
confidence: 99%
“…rapid onset, needle-free administration, effective anxiolysis), such as with the pre-treatment or co-administration with lidocaine. 57,[60][61][62][63] The administration of the IN formulation of ketorolac containing lidocaine has been associated with nasal pain in 5-20% of patients, with the degree of pain intensity rated as "mild" in one study. 14,48,49,51 However, further research is necessary to better describe the effect of lidocaine or…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Although the intranasal route for midazolam is well studied, a significant proportion of preterm babies at TEA require nasal cannula or CPAP. Utilizing the intranasal route might pose problems with instilling and briefly disconnecting the nasal interface and causing discomfort and burning sensation intranasally [18][19][20]. Hence, we proposed a novel approach of using buccal midazolam as the agent of choice for providing procedural sedation for MRI in patients who were not on mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%